2020
DOI: 10.3389/fnagi.2020.592979
|View full text |Cite
|
Sign up to set email alerts
|

Regional Gray Matter Volume Identifies High Risk of Unsafe Driving in Healthy Older People

Abstract: In developed countries, the number of traffic accidents caused by older drivers is increasing. Approximately half of the older drivers who cause fatal accidents are cognitively normal. Thus, it is important to identify older drivers who are cognitively normal but at high risk of causing fatal traffic accidents. However, no standardized method for assessing the driving ability of older drivers has been established. We aimed to establish an objective assessment of driving ability and to clarify the neural basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Thus, based on our previous study, we hypothesized that structural abnormalities in brain regions involved in attentional functions might be associated with the risk of unsafe driving among healthy older drivers. Previously, we exploratively built a classification model that could dissociate unsafe drivers from safe drivers with an accuracy of 87.5% using gray matter volume data 12 . Our analysis of the features that contributed to this model showed that gray matter volume in the frontal eye field and inferior parietal lobule (IPL) were strongly associated with a high risk of unsafe driving among healthy older people 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, based on our previous study, we hypothesized that structural abnormalities in brain regions involved in attentional functions might be associated with the risk of unsafe driving among healthy older drivers. Previously, we exploratively built a classification model that could dissociate unsafe drivers from safe drivers with an accuracy of 87.5% using gray matter volume data 12 . Our analysis of the features that contributed to this model showed that gray matter volume in the frontal eye field and inferior parietal lobule (IPL) were strongly associated with a high risk of unsafe driving among healthy older people 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we exploratively built a classification model that could dissociate unsafe drivers from safe drivers with an accuracy of 87.5% using gray matter volume data 12 . Our analysis of the features that contributed to this model showed that gray matter volume in the frontal eye field and inferior parietal lobule (IPL) were strongly associated with a high risk of unsafe driving among healthy older people 12 . Since the frontal eye field and IPL constitute the dorsal attention network (DAN), this finding suggested that the DAN is more strongly involved in the risk of unsafe driving in healthy older people than other attention‐related networks, such as the ventral attention network (VAN) and the default mode network (DMN).…”
Section: Introductionmentioning
confidence: 99%
“…Toyota Central Research and Keio University teams investigated the relationship between brain and driving performances with 39 and 32 participants, respectively (Sakai et al, 2012 ; Yamamoto et al, 2020b ). The present study enrolled 90 participants, which may be not regarded small but relatively large for the analyses of driving performances using actual motor vehicles connected with MRI data.…”
Section: Discussionmentioning
confidence: 99%
“…Other cerebral sites were not investigated. Very recently, parts of DSPs were investigated using 32 participants and vehicle stability (acceleration and braking without knocking) at an intersection was reported to correlate to the volumes of several cortical regions including the superior frontal sulcus (Yamamoto et al, 2020b ). Elucidating the relationship between brain volume and DSP has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Aydogan et al [ 19 ] have found that people who reported higher risk behavior related to alcohol, smoking, sex, or driving had a lower gray matter volume in areas such as the striatum, putamen, ventromedial, and dorsolateral prefrontal cortex, insula, and cerebellum. In another recent study, Yamamoto et al [ 117 ] have evaluated, using realistic driving situations, risky driving at intersections with stop signs in a group of older adults without cognitive impairment. The best predictors for classifying risky and non-risky drivers were age and the gray matter volume of areas related to executive functions, cognitive control, and incentive processing in the frontal and parietal cortices.…”
Section: Discussionmentioning
confidence: 99%